2006
DOI: 10.1097/01.ana.0000191280.05170.0f
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of Sodium in Critically Ill Adult Neurologic Patients

Abstract: Disorders of sodium and water balance are common in critically ill adult neurologic patients. Normal aspects of sodium and water regulation are reviewed. The etiology of possible causes of sodium disturbance is discussed in both the general inpatient and the neurologic populations. Areas of importance are highlighted with regard to the differential diagnosis of sodium disturbance in neurologic patients, and management strategies are discussed. Specific discussions of the etiology, diagnosis, and management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
15

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 59 publications
(72 reference statements)
1
105
0
15
Order By: Relevance
“…the incidence of csWs among all the patients was greater than that of sIADH, which is in agreement with reports from various other authors, who also observed a greater prevalence of csWs, compared to sIADH in neurological patients 1,2,4,5,10,18,30 . the coexistence of DI and csWs (mixed syndrome) observed in our patients has also been described by yamaki et al 17 , who studied two patients postoperatively following surgery for pituitary tumor and observed the presence of severe natriuresis and hyponatremia in a study patient who developed DI (fluid loss >2.36 ml/kg/h), which led the authors to conclude that hyponatremia resulting from csWs in intracranial diseases may develop in patients with DI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…the incidence of csWs among all the patients was greater than that of sIADH, which is in agreement with reports from various other authors, who also observed a greater prevalence of csWs, compared to sIADH in neurological patients 1,2,4,5,10,18,30 . the coexistence of DI and csWs (mixed syndrome) observed in our patients has also been described by yamaki et al 17 , who studied two patients postoperatively following surgery for pituitary tumor and observed the presence of severe natriuresis and hyponatremia in a study patient who developed DI (fluid loss >2.36 ml/kg/h), which led the authors to conclude that hyponatremia resulting from csWs in intracranial diseases may develop in patients with DI.…”
Section: Discussionsupporting
confidence: 93%
“…this suggests that csWs is the principal cause of natriuresis in these patients 2,10,30 . the present study also shows that most of the patients who developed hyponatremia and natriuresis presented no increase in plasma AVP levels, suggesting that the probable cause of natriuresis in these patients is csWs.…”
Section: Discussionmentioning
confidence: 78%
“…6,11,15,19 The etiology of hypernatremia may not be strictly defined in patients with TBI, and this condition may be due to hyperosmolar therapy; hypovolemia; insensible free water losses; or high sodium load in intravenous fluids, feeds, or medications. 20 Additionally, hypothalamic dysfunction not resulting in overt diabetes insipidus may contribute to hypernatremia after TBI. 15 In the present study, even mild and moderate hypernatremia was independently associated with increased mortality, and this relationship was maintained in patients who did not receive mannitol to treat cerebral edema.…”
Section: Fig 1 Kaplan-meier Curve Showing Survival Rates By Severitmentioning
confidence: 99%
“…Patients with polytrauma and traumatic brain injury are the most critically ill patients, and hyponatremia is frequently seen in these patients [2][3][4]. Hyponatremia is one of the common causes of secondary brain injury [5].…”
Section: Introductionmentioning
confidence: 99%